Kinetics studies of the superoxide-mediated electron transfer reactions between rubredoxin-type proteins and superoxide reductases - Auchère, Françoise (2013)
J Biol Inorg Chem (2006) 11: 433–444 DOI 10.1007/s00775-006-0090-0